Convergent specialization – the sharing of pollinators by sympatric genera of sexually deceptive orchids. (24th April 2013) - Phillips, Ryan D.; Xu, Tingbao; Hutchinson, Michael F.; Dixon, Kingsley W.; Peakall, Rod; Santamaria, Luis
Summary Pollinator sharing can offer powerful insights into the floral traits associated with the evolution of a pollination system and the consequences of floral differences for pollinator behaviour. Here, we investigate the first known case of pollinator sharing between two sexually deceptive plant genera. Floral manipulations were used to test the importance of floral traits for pollinator behaviour and pollination efficiency. We also explored the ecological differences enabling species co‐occurrence. Drakaea livida and Caladenia pectinata (Orchidaceae) exhibit dramatic differences in floral display and the insectiform appearance of the labellum, yet both are pollinated by sexually attracted males of the thynnine wasp Zaspilothynnis nigripes. Because of the prevalence of cryptic species in some genera of thynnine wasps, we confirmed pollinator sharing by a mark–recapture study and sequencing of the mtDNA CO1 region. Floral dissections revealed that semiochemicals used to attract the pollinator are released from the labellum in D. livida and sepaline clubs in C. pectinata. Drakaea livida was more efficient at converting pollinator attraction into potential pollen deposition leading to higher fruit set. Floral manipulations showed that pollinator contact with the labellum increases when it is the point of semiochemical release. However, sexual attraction to the labellum remained infrequent in C. pectinata in all experimental treatments. While their distribution and climatic range show extensive overlap, the differences in edaphic requirements of the two orchid species suggest that they rarely co‐occur. Therefore, the potential cost of sharing the same pollinator species is not realized. Synthesis. This case of pollinator sharing confirms that morphological traits do not place a strong constraint on the evolution of sexual deception. However, interspecific differences in floral traits have important consequences for converting attraction into pollination, suggesting that selection can act to increase efficiency at multiple steps of the pollination process. This system provides a novel opportunity to elucidate the chemical, visual and morphological adaptations underpinning the evolution of sexual mimicry.